Fetal growth is associated with CpG methylation in the P2 promoter of the IGF1 gene - Le Stunff, Catherine (Clin Epigenetics, 2018)
BACKGROUND: There are many reasons to think that epigenetics is a key determinant of fetal growth variability across the normal population. Since IGF1 and INS genes are major determinants of intrauterine growth, we examined the methylation of selected CpGs located in the regulatory region of these two genes. METHODS: Cord blood was sampled in 159 newborns born to mothers prospectively followed during their pregnancy. A 142-item questionnaire was filled by mothers at inclusion, during the last trimester of the pregnancy and at the delivery. The methylation of selected CpGs located in the promoters of the IGF1 and INS genes was measured in cord blood mononuclear cells collected at birth using bisulfite-PCR-pyrosequencing. RESULTS: Methylation at IGF1 CpG-137 correlated negatively with birth length (r = 0.27, P = 3.5 × 10(−4)). The same effect size was found after adjustment for maternal age, parity, and smoking: a 10% increase in CpG-137 methylation was associated with a decrease of length by 0.23 SDS. CONCLUSION: The current results suggest that the methylation of IGF1 CpG-137 contributes to the individual variation of fetal growth by regulating IGF1 expression in fetal tissues. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13148-018-0489-9) contains supplementary material, which is available to authorized users.